EFISIENSI PENGGUNAAN PUPUK ANORGANIK AKIBAT PENGGUNAAN PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG (Zea mays L) DI TANAH ULTISOL - Roswita Oesman (Jurnal Pertanian Tropik, 2017)
The research effects to obtain inorganic fertilizer use efficiency to the use of organic fertilizer onthe growth and yield of maize (Zea mays L) in Ultisol. This research was conductedat the experimental field, the Laboratory for Research and Technology Faculty ofAgriculture, University of North Sumatra, Medan from August to November 2016. Thethe design used in this study is a randomized block design factorial using two factors:organic fertilizers (O) with treatment as follows: O0 = Without organic fertilizers,O1 = 100% of doses of organic fertilizer, O2 = 75% of doses of organic fertilizer, O3= 50% of doses of organic fertilizer, O4 = 25% of doses of organic fertilizer.inorganic fertilizer application (A) with treatment as follows: A0 = Withoutinorganic fertilizers, A1 = 100% of doses of inorganic fertilizer recommendations,A2 = 75% of doses of inorganic fertilizer recommendations, A3 = 50% of doses ofinorganic fertilizer recommendations, A4 = 25% of doses of inorganic fertilizerrecommendations. The variables measured were: plant height, shoot dry weight, rootdry weight, dry seed weight. Results showed that 100% Organic fertilizer canincrease growth and yield of corn were higher in soil ultisol. This is indicated bytheir real influence on the growth of plant height ages 8 and 12 WAP, the weight ofdry seed, uptake of N and P, but no significant effect on shoot dry weight, root dryweight and uptake K. Inorganic fertilizer application of 100% can increase growthand yield of corn was higher in soil ultisol. This is indicated by their real influenceon the growth of plant height age 8 WAP, root dry weight and the weight of dry seed,but did not significantly affect plant height age of 12 WAP, shoot dry weight, uptakeof N, P and K. The interaction of the two combination treatments showed significantlyeffect on the weight of dry seed.